The Influence of Profitability, Solvency, Auditor’s Opinion and Reputation to Audit Delay (The Empirial Study of Manufacturing Companies Listed on Indonesia Stock Exchange 2012-2013) - ., Triandi; Hadiyanti, Rizki (Institut Bisnis dan Informatika Kesatuan, 2017)
The presentation of financial statements of a go public company towards its concerned parties requires a punctual publishing of financial statements. Punctuality reflects the qualitative characteristics of financial statements reporting according to the accounting principal that is generally used in Indonesia. Such qualitative characteristic is relevant, meaning that the information contained in the financial statements must be able to influence the decision makers, so the reports must be delivered punctually. Relevant has the close connection to timeliness of reporting. Timeliness also related to the time difference between date of financial statements and date of auditor’s report, which indicates the length of time of auditing settlements, or called as audit delay as the dependent variable. This study aims to measure empirically the factors affecting audit delay of the listed manufacturing companies on Indonesia Stock Exchange. They are profitability, solvency, auditor’s opinion and reputation as the independent variables. The samples of this research consist of 147 manufacturing companies in Indonesia Stock Exchange during 2012-2013 and selected by purposive sampling. The data used is secondary data; which are audited financial statements of 147 samples. The data analysis used methods to prove the hypothesis are descriptive statistics, classic assumptions test, multiple regression models, and the determinant coefficient. The study finds that three out of four independent variables influence insignificantly to audit delay; they are profitability, solvency and auditor’s opinion. Only auditor reputation influences audit delay significantly. The simultaneous testing concluded that all independent variables influence the dependent variable significantly.